A Compact CPW-Fed UWB Antenna with Dual Band-Notched Characteristics. (27th November 2013) - Wu, Aiting; Guan, Boran
Abstract : A compact CPW-fed planar UWB antenna with dual band-notched property is presented. The dual band rejection is achieved by etching a C-shaped slot on the radiation patch and two L-shaped parasitic strips in the ground plane. The experimental and measured results show that the proposed antenna exhibits an impedance bandwidth over an ultrawideband frequency range from 2.4 to 12.5 GHz with VSWR less than 2, except for two stopbands at 3.3 to 3.75 GHz and 5.07 to 5.83 GHz for filtering the WiMAX and WLAN signals, respectively. It also demonstrates a nearly omnidirectional radiation pattern. The fabricated antenna has a tiny size, only 32 mm × 32 mm × 0.508 mm. The simulated results are compared with the measured performance and show good agreement. The simple structure, compact size, and good characteristics make the proposed antenna an excellent candidate for UWB applications.